THE ANALYSIS OF PEDAGOGICAL CONTENT KNOWLEDGE (PCK) SUBSTANCE IN PRE-SERVICE SCIENCE TEACHERS' SKILLS TO ANALYZE ESSENTIAL MATERIAL OF SCIENCE - Aris Rudi Purnomo; Siti Nurul Hidayati (JURNAL PENA SAINS, 2018)
Skills to analyze essential material are compulsory for pre-service science teachers, especially by the substance of PCK (elements for the professionalism of science teachers). Therefore, this study aimed at describing the ability of pre-service science teachers in analyzing the essential material of science regarding PCK substance, namely organizing science material. This observational research used a rubric to record quantitative data and research note for qualitative data. The data then analyzed descriptively. As a result, the competence of pre-service science teachers in analyzing the essential material of science is good enough. However, there are only some shortcomings related to the use of propositions in the concept mapping, the connection between concept domain, and extracting learning indicators that can suffice basic of competence.